In silico Studies for Tridax procumbens Linn Phyto constituents with Anti-inflammatory Receptors (Asian Journal of Pharmaceutics (AJP), 2022)
Introduction: A wound is categorized as a breakdown or opening of the skin, which could lead tomalfunctioning of the skin. Materials and Methods: Interleukin-1 receptor-associated kinases are keycomponents in the signal transduction pathways utilized by interleukin-1 receptor and interleukin-18 receptor.Results and Discussion: The critical role of IRAK-4 in inflammatory processes, and modulation of IRAK-4kinase activity presents an attractive therapeutic approach for the treatment of inflammatory diseases. To identifythe potent IRAK-4 inhibitors with new anti-inflammatory therapeutic agents from selected herbal plants andtheir extract with the help of in-silico data. Conclusion: In the present study, we have investigated in silicocomputational studies for Tridax procumbens phytoconstituents against the molecular targets involved in theanti-inflammatory process. The molecular docking interactions show good binding affinity against the moleculartargets of the anti-inflammatory target, namely, ILAK4. Among the ligands docked against ILAK4, Nodakenin(14), and Apigenin 7-O-β-D-glucoside (16) showed excellent free energy binding with dock score values of −9.4and −10 kcal/mol, respectively. These results suggest that further mechanistic studies are to be done for thesephytoconstituents against anti-inflammation.